Transcriptomic Insights Into Root Development and Overwintering Transcriptional Memory of Brassica rapa L. Grown in the Field - Liu, Lijun; Pu, Yuanyuan; Niu, Zaoxia; Wu, Junyan; Fang, Yan; Xu, Jun; Xu, Fang; Yue, Jinli; Ma, Li; Li, Xuecai; Sun, Wancang (Frontiers in Plant Science, 2022)
As the only overwintering oil crop in the north area of China, living through winter is the primary feature of winter rapeseed. Roots are the only survival organ during prolonged cold exposure during winter to guarantee flowering in spring. However, little is known about its root development and overwintering memory mechanism. In this study, root collar tissues (including the shoot apical meristem) of three winter rapeseed varieties with different cold resistance, i.e., Longyou-7 (strong cold tolerance), Tianyou-4 (middle cold tolerance), and Lenox (cold-sensitive), were sampled in the pre-winter period (S1), overwintering periods (S2–S5), and re-greening stage (S6), and were used to identify the root development and overwintering memory mechanisms and seek candidate overwintering memory genes by measuring root collar diameter and RNA sequencing. The results showed that the S1–S2 stages were the significant developmental stages of the roots as root collar diameter increased slowly in the S3–S5 stages, and the roots developed fast in the strong cold resistance variety than in the weak cold resistance variety. Subsequently, the RNA-seq analysis revealed that a total of 37,905, 45,102, and 39,276 differentially expressed genes (DEGs), compared to the S1 stage, were identified in Longyou-7, Tianyou-4, and Lenox, respectively. The function enrichment analysis showed that most of the DEGs are significantly involved in phenylpropanoid biosynthesis, plant hormone signal transduction, MAPK signaling pathway, starch and sucrose metabolism, photosynthesis, amino sugar and nucleotide sugar metabolism, and spliceosome, ribosome, proteasome, and protein processing in endoplasmic reticulum pathways. Furthermore, the phenylpropanoid biosynthesis and plant hormone signal transduction pathways were related to the difference in root development of the three varieties, DEGs involved in photosynthesis and carbohydrate metabolism processes may participate in overwintering memory of Longyou-7 and Tianyou-4, and the spliceosome pathway may contribute to the super winter resistance of Longyou-7. The transcription factor enrichment analysis showed that the WRKY family made up the majority in different stages and may play an important regulatory role in root development and overwintering memory. These results provide a comprehensive insight into winter rapeseed's complex overwintering memory mechanisms. The identified candidate overwintering memory genes may also serve as important genetic resources for breeding to further improve the cold resistance of winter rapeseed.